Deconstructing type 2 diabetes self‐management of Australian Pacific Islander women: Using a community participatory research and talanoa approach. (27th September 2021) - Akbar, Heena; Gallegos, Danielle; Anderson, Debra; Windsor, Carol
Abstract: Community‐based participatory research using culturally appropriate talanoa approaches provided the framework to explore diabetes self‐management of Australian Pacific Islander (API) women living with type 2 diabetes in South‐East Queensland. Data collection included interviews with key informants (21), in‐depth interviews with API women with diabetes (10), talanoa group discussions (7) and monthly steering committee meetings. Using an interpretive‐constructionist lens and the interpretations of community members, four cultural constructs in diabetes self‐management emerged: self‐identity, spirituality, stigma and denial, and structural factors. Self‐identity connected the women to their Pacific heritage that framed their collective roles as primary caregivers in the community. This gave the women a strong sense of belonging and helped maintain cultural, family and relational connections which were important for their day‐to‐day management of diabetes. Although spirituality through religion supported the women to cope with their diabetes a total reliance on God resulted in disengagement with self‐care. Shame associated with disclosure also prevented effective self‐management. Finally, structural factors such as access to healthcare, poor health literacy and cultural barriers associated with obesogenic environments impeded women from seeking appropriate diabetes care. However, family and community were critical in ensuring women were supported with their diabetes self‐management. The findings highlight the importance of engaging families in healthcare planning decisions in the development of culturally responsive models of diabetes support care for API women with type 2 diabetes.